Assessment of nested-parallel task model under real-time scheduling on multi-core processors. (28th November 2019) - Lokhande, Mahesh; Atique, Mohammad
Real-time applications contain numerous time-bound parallel tasks with enormous computations. Parallel models, not the sequential models, have the capability to handle intra-task parallelism and accomplish such tasks in a specific time or before. Previous researchers presented the task models for parallel tasks, but not for the nested-parallel tasks. This paper deals with the real-time scheduling of periodic nested-parallel tasks having an implicit deadline on multi-core processors. Initially, an nested-parallel task model is developed. Next, a novel task disintegration technique is studied where the MAM's ratio is defined to categorise the segments. It is theoretically proved that the discussed disintegration technique achieved a speedup factor of 4.30 and 3.40 when the tasks, after disintegration, are scheduled under partitioned deadline monotonic (DM) and global earliest deadline first (EDF) scheduling, respectively. Further, considering the overhead factor ( β ) for non-preemptive global EDF scheduling, disintegration technique is analysed and achieved a speedup factor of 3.73 (for β = 1). The proposed disintegration technique is assessed through the simulations thereby indicating the adequacy of derived speedup factors.